2023
DOI: 10.3390/su151813506
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Digital Transformation on ESG Performance Based on the Mediating Effect of Dynamic Capabilities

Xin Su,
Shengwen Wang,
Feifei Li

Abstract: The United Nations Development Summit in 2015 adopted the “2030 Agenda for Sustainable Development”, establishing a framework for Sustainable Development Goals (SDGs) with the aim of achieving coordinated economic, social, and ecological development worldwide by 2030. The “environmental, social, and governance” (ESG) approach is important within the concept of SDGs and is the subject of increasing attention from scholars. Despite China’s significant contributions to the SDGs, it still faces numerous challenges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 53 publications
0
6
0
1
Order By: Relevance
“…Digital transformation provides companies with more efficient data collection, storage, and analysis technologies that can be used to help them better monitor their environmental impacts, address the fragmentation of environmental data, and improve their ESG performance (Wang & Esperança, 2023). Digital transformation can bring about changes and optimization in organizational structure, internal management, and other governance aspects within the enterprise, so that it can have more dynamic capabilities, helping it to improve ESG performance (Su et al, 2023). A study based on the European Union shows that a 1% increase in digital inclusion results in a minimal .001% increase in the ESG performance (Kwilinski et al, 2023).…”
Section: Link Between Digitalization and Esg Performancementioning
confidence: 99%
“…Digital transformation provides companies with more efficient data collection, storage, and analysis technologies that can be used to help them better monitor their environmental impacts, address the fragmentation of environmental data, and improve their ESG performance (Wang & Esperança, 2023). Digital transformation can bring about changes and optimization in organizational structure, internal management, and other governance aspects within the enterprise, so that it can have more dynamic capabilities, helping it to improve ESG performance (Su et al, 2023). A study based on the European Union shows that a 1% increase in digital inclusion results in a minimal .001% increase in the ESG performance (Kwilinski et al, 2023).…”
Section: Link Between Digitalization and Esg Performancementioning
confidence: 99%
“…Ren et al 25 have found that digital finance can influence corporate ESG performance through green innovation and external regulation. Su et al 26 take Chinese A-share listed companies from 2011 to 2020 as samples and believe that DT has a positive impact on ESG performance, while dynamic capability plays a positive intermediary role. Wu and Li 27 also adopted a multiple linear regression model to discuss the positive impact of DT on ESG performance and affirm the positive effects of green innovation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…DT contributes significantly to reducing pollutant emissions and protecting the environment, enabling existing problems to be solved in a more ecofriendly manner [42]. DT can support ESG innovation by standardizing and modularizing corporate resources and processes to reduce costs and improve business models [43]. The following research hypotheses were derived based on these preceding studies.…”
Section: Digital Transformation and Esg Managementmentioning
confidence: 99%